Contradiction and crisis in cognitive capitalism - Moreno Gálvez, Francisco Javier (2016)
In the reorganization of capitalism that took place in the 1970s, new information and communication technologies played a fundamental role, allowing an intensive use of knowledge, a role that we can trace in its continuity to this day. In the last decades we witness the development of a contradictory tension between the tendency towards privatization, characteristic of cognitive capitalism, and the democratizing tendency of the social economy of knowledge. This article attempts to analyze this tension pointing to the consequences for development models that come into dispute in the current global context.